(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Robusta coffee is a superior commodity from Tanggamus District which has promising market opportunities.The research was conducted in one of the Robusta coffee centers in Tanggamus District, in Argopeni and Datarajan village, Sumberejo and Ulubelu sub-district. The purposes of this research were (1) to determine the income and profits of grade 4 coffee farmers in Robusta coffee plantations in Tanggamus Regency, (2) to find out the best decision for farmers in continuing process of grade 4 coffee into ground coffee. The sampling tech- nique of this research used purposive from 68 coffee farmers. The techniques of data collection were structured interviews using questionnaires and direct obser- vation. Farm business analysis was used to determine the income and profits of coffee bean farmers, differential analysis was used for the best decision to sell coffee beans or to process them into ground coffee. The results of the study showed that coffee farm bussiness of the grade 4 coffee coffee beans earned Rp24,532,081/ year and earned a profit of Rp10,503,837/1.390 kg/year farmers are better if they continue the production process from the grade 4 coffee into ground coffee. The further processing of ground coffee earned profit of Rp33,002,568/year.